Photoreceptor degeneration induced by the expression of simian virus 40 large tumor antigen in the retina of transgenic mice. - al-Ubaidi, M R (1992)
Expression of the viral oncogene encoding the simian virus 40 (SV40) large tumor antigen (T antigen) typically promotes tumorigenesis in mammalian cells. To generate transgenic mice that express T antigen in rod photoreceptors, a chimeric construct consisting of a mouse opsin promoter fragment fused to the coding region of SV40 T antigen was generated. Expression of T antigen in the transgenic retina began at early stages of postnatal development concomitant with expression of endogenous opsin. Instead of inducing hyperplasia or tumor formation, T-antigen expression caused a rapidly progressing photoreceptor degeneration. The degeneration was accompanied by sustained DNA synthesis in photoreceptor cells, as evidenced by incorporation of [3H]thymidine and by the appearance of mitotic figures at postnatal day 10, a stage when nontransgenic photoreceptor cells are postmitotic and quiescent. Although transgenic photoreceptor cells undergo S phase and enter mitosis, the consequences of T-antigen expression are not proliferation and tumorigenesis but proliferation and cell death.